2019
DOI: 10.1177/1751143719870121
|View full text |Cite
|
Sign up to set email alerts
|

A survey examining the use of mechanical insufflation-exsufflation on adult intensive care units across the UK

Abstract: Introduction Despite potential benefits, it is not known how widely physiotherapists use mechanical insufflation-exsufflation devices on UK adult intensive care units. This survey aimed to describe mechanical insufflation-exsufflation use in UK adult intensive care units. Methods Cross-sectional electronic survey of physiotherapists working in a permanent post on adult intensive care units. Results One hundred and sixty-six complete surveys were available for analysis, reflecting a diverse geographical spread.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…We found use of MI-E in invasively ventilated patients uncommon in the Netherlands (21%) compared to Canada (64% of the ICUs) [ 17 ] and the United Kingdom (98% of the ICUs) [ 27 ]. These surveys report MI-E to be used for invasively ventilated patients during weaning from invasive ventilation [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found use of MI-E in invasively ventilated patients uncommon in the Netherlands (21%) compared to Canada (64% of the ICUs) [ 17 ] and the United Kingdom (98% of the ICUs) [ 27 ]. These surveys report MI-E to be used for invasively ventilated patients during weaning from invasive ventilation [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Florence Nightingale Faculty of Nursing, Midwifery and Palliative Care, King's College London, London, UK. 13 Lane Fox Respiratory Unit, Guy's and Thomas' Foundation NHS Hospital Trust, London, UK.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing interest in the role of MI-E for invasively ventilated critically ill adults but to date adoption and application of this technique is variable [11][12][13]. The primary aim of this scoping review is to map emerging and current evidence, on MI-E in an ICU setting, thus adding to previous Cochrane Review findings [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the role of cough augmentation techniques in prevention of extubation failure is unclear and additional robust research, including understanding intervention safety and intensity, is essential. Furthermore, despite emerging evidence in the intubated population a recent UK survey has highlighted limited adoption of this device in the intubated population [128]. Analgo-sedation and NIV Lara Pisani provided a clear overview of the available medications and the role they should play to facilitate NIV.…”
Section: Take-home Messagesmentioning
confidence: 99%